Optimization of X-Ray Imaging Systems for Enhanced Image Quality and Reduced Radiation Dose - Taih, Mohammed mahmoud; Hatim, Mustafa Mohammed (American Journal of Botany and Bioengineering, 2025)
This paper describes a comprehensive study on optimizing x-ray imaging systems to improve image quality and to reduce radiation dose. The study involves a variety of optimization methodologies, including theoretical analysis using a cascade imaging systems model, computational modeling in imaging characteristics, laboratory measurements on fluorescent x-ray tubes and phosphor screens, and imaging experiments with clinically used phosphor-based systems and a phase contrast x-ray system. It is found that optimization methodologies developed in this study can lead to notable improvements in image quality with reduced radiation dose in a variety of x-ray imaging systems. X-ray imaging is an invaluable tool in medicine, biology and a variety of industrial applications. Its significance continues to grow as technology advances and new techniques emerge. For most of these applications, however, either the x-ray image quality needs to be improved, or the radiation dose needs to be reduced; often both are required. This is a grand-challenge problem, because it involves a large coupled system encompassing x-ray sources, imaging detectors, object-sample materials and their shapes and motions, image-processing algorithms and human observer tasks. In addition, heightened public awareness about x-ray safety has made the manufacturers of x-ray imaging devices accountable for the maximum possible safety in device operation. Current x-ray imaging devices are designed to prevent accidental overexposure to patients by incorporating x-ray sources and fixed physical structures that limit radiation exposure. However, little has been done to the cascade character of x-ray photons throughout the device before they are absorbed in an imaging medium. In this paper, a detailed cascading-system model is developed to describe the x-ray imaging process, taking into account not only the device components but also imaging characteristics, such as geometric unsharpness, focal spot size, and x-ray scatter.